MEMBANGUN KONSEP HYBRID CONTRACT UNTUK PENGEMBANGAN PRODUK MULTI FACED PERBANKAN SYARIAH - Isyrokh Fuaidi dan Muhammad Kholiluzzair (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) IPMAFA, 2016)
The Contract is becoming mainstream product transaction of syariah banking. This during, the faced problem basic of syariah banking is respond able manner fiqh muamalah about issue of challenge model syariah banking transaction will go on for grow up in dinamic. As is product syariah banking much an appliying for double contract and contract in the lest experience alteration from the original basic types of contract. This research is an applying for Normative cum Empiris approach. That is trying to reviewing it with the literature method and religious theory basics, then try to contextualize as respects perceivable, like normative type into an applicable reality. The method direction will be used not only normative but also can be able problem recerve in an empirical.